PEMBERDAYAAN KELOMPOK PKK MELALUI APLIKASI DETEKSI DAN PROGRAM GACOR DI KECAMATAN TULUNG SELAPAN - Sari, Indah; Soleha, Siti; Martadinata, Fendri; Rizqillah, Cantika Arzsyah; Rusera, Siti Akhirunnisah; Putri, Raizha Fasillah (Universitas katolik Musi Charitas, 2025)
Purpose: The implementation of community service activities aligned with the Sustainable Development Goals (SDGs), Key Performance Indicators (IKU), Asta Cita, and the National Research and Innovation Roadmap (RIRN) aims to reduce health risks associated with formalin-contaminated food, enhance public health awareness, strengthen practical understanding of the program application system, and increase knowledge related to formalin through structured training. These efforts contribute to the collective vision of achieving Indonesia Emas 2045. Design/Methodology/Approach: PKK members were positioned as community-based educators and facilitators in the prevention and control of formalin contamination in food products. Program effectiveness and efficiency were evaluated using a mixed-methods approach, including pre-test and post-test assessments, interviews, and direct observations. The program involved 17 PKK members who participated in training sessions on formalin removal techniques and the use of a formalin detection application. Findings: The evaluation results indicate a measurable improvement in participants’ knowledge following the training program. The average pre-test score increased from 78 to an average post-test score of 85 after participants received instruction on formalin reduction techniques in salted fish and the utilization of a web-based formalin detection application. Practical Implications: Formalin content in salted fish can be effectively reduced by soaking the product in warm water at a temperature of 40°C for 15 minutes. Formalin detection can be supported through the use of the gacor.web.id application, which facilitates early identification and community-level monitoring of food safety risks. Originality/Value: This program offers a practical, community-driven model for preventing and monitoring formalin contamination in food, integrating simple treatment methods with digital detection tools to strengthen food safety awareness at the grassroots level.